From public service access to service quality: The distributive politics of piped water in Bangalore. (March 2022) - Kumar, Tanu; Post, Alison E.; Ray, Isha; Otsuka, Megan; Pardo-Bosch, Francesc
Highlights: The intermittent delivery of services such as water and electricity affects hundreds of millions of people, but is understudied in political economy. We show how to study the allocation of intermittency services through a study of water flows in Bangalore, India. We highlight the specific facets of intermittency that are salient to citizens and that may be manipulated independently. Through an analysis of water service quality in eastern Bangalore, we show how infrastructure networks shape allocations of water and intermittency. Water flows through pipes more frequently and predictably in low-income neighborhoods than in more affluent neighborhoods in our study area. Abstract: Public service access in low- and middle- income countries is shaped by how much governments spend on services and where they choose to prioritize delivery. Accordingly, the local public goods and distributive politics literatures are largely focused on government spending and patterns of access. We argue that, even after access is granted, service quality can vary dramatically, and may vary with socio-economic and political characteristics. We provide one of the first analyses of a key dimension of service quality: intermittency, which affects vital services such as water and electricity for hundreds of millions of people. We illustrate how to study it by highlighting the specific facets of intermittency that must be managed within the network; we show that these dimensions may be manipulated separately, and that infrastructure network structure shapes the allocation of intermittency. The literature from urban India shows that access to water connections (like access to many other local public goods) is typically associated with higher socio-economic status. In contrast, we find that in our study sites in Bangalore, water flows through pipes more frequently and predictably in low-income areas—thereby underscoring the importance of studying intermittency, and service quality more generally, as phenomena distinct from access.